The Effect of Excavation Disturbance on the Stability of Bedding Cataclastic Rock Mass High Slope Containing Multimuddy Interlayers - Fei Liu; Jiaming Zhang; Pengzheng Guo; Wenlian Liu; Zhiqiang Wang; Jipu Chen (Advances in Civil Engineering)
In China, slope engineering occasionally faces landslides in rocky slopes containing muddy interlayers, primarily triggered by excavation activities. These incidents lead to considerable human casualties and substantial economic losses. However, existing studies predominantly concentrate on the excavation-induced impacts on the stability of rocky slopes characterized by single-layered soft and weak interlayers. Conversely, reports on how excavation influences the stability of bedding cataclastic rock mass high slope containing multimuddy interlayers remain notably absent in the literature. Moreover, unloading due to excavation can swiftly compromise the mechanical integrity and overall quality of the rock mass, consequently impacting the stability of slopes postexcavation. Therefore, this paper modeled the unstable slope excavated at a waste incineration power plant in Yuxi, Yunnan, using the finite element strength reduction method. This approach was employed to comprehensively simulate the entire process of artificial multilevel excavation in a bedding cataclastic rock mass high slope containing multimuddy interlayers. This study investigated the impact of multilevel artificial excavation on slope stability by thoroughly considering factors including alterations in slope morphology, unloading effects, and the degradation of geotechnical parameters. The research yielded the subsequent conclusions. Multimuddy interlayers were the key to the slope’s instability. For slopes subjected to such multilevel excavation, efforts were made to minimize the exposure of muddy interlayers. Slopes above exposed muddy interlayers did not require additional support, while those below needed prioritized reinforcement. The likely instability mode of the actual slope was local destabilization leading to landslides. Furthermore, when using numerical simulation methods to study the impact of excavation disturbances on the stability of such slopes, it was necessary to consider the deterioration of geotechnical parameters to obtain results more reflective of actual conditions. These research findings provided valuable theoretical and empirical support for studies on similar excavated slopes.